Evaluating Optimism: Developing Children’s Version of Optimistic Attributional Style Questionnaire - Gordeeva T.O.,; Sychev O.A.,; Osin E.N., (Культурно-историческая психология, 2017)
People differ significantly in how they usually explain to themselves the reasons of events, both positive and negative, that happen in their lives. Psychological research shows that children who tend to think optimistically have certain advantages as compared to their pessimistically thinking peers: they are less likely to suffer from depression, establish more positive relationships with peers, and demonstrate higher academic achievements. This paper describes the process of creating the children’s version of the Optimistic Attributional Style Questionnaire (OASQ-C). This technique is based on the theory of learned hopelessness and optimism developed by M. Seligman, L. Abramson and J. Teas dale and is an efficient (compact) tool for measuring optimism as an explanatory style in children and adolescents (9-14 years). Confirmatory factor analysis revealed that this technique is a two-factor structure with acceptable reliability. Validity is supported by the presence of expected correlations between explanatory style and rates of psychological well-being, dispositional optimism, positive attitude to life and its aspects, depression, and academic performance. The outcomes of this technique are not affected by social desirability. The developed questionnaire may be recommended to researchers and school counsellors for evaluating optimism (optimistic thinking) as one of the major factors in psychological well-being of children; it may also be used in assessing the effectiveness of cognitive oriented training for adolescents.